Unleashing MR DARCY - Wilson, Teri (England : Harlequin MIRA, 2014)
It is a truth universally acknowledged that a single woman teetering on the verge of thirty must be in want of a husband. Not true for Manhattanite Elizabeth Scott. Instead of planning a walk down the aisle, she's crossing the pond with the only companion she needs--her darling dog, Bliss. Caring for a pack of show dogs in England seems the perfect distraction from the scandal that ruined her teaching career, and her reputation, in New York. What she doesn't count on is an unstoppable attraction to billionaire dog breeder Donovan Darcy. The London tycoon's a little bit arrogant, a whole lot sexy...and the chemistry between them is disarming. When passion is finally unleashed, might Elizabeth hope to take home more than a blue ribbon?
Keywords: English fiction; Man-woman relationships -- Fiction; Love stories